(untitled) (Intent Research Scientific Journal, 2024)
In the context of a mixed type of educational interaction in teaching Russian language and literature, the role of new form texts (polycode, creolized, nonlinear) is increasing as a means of forming students’ linguistic, communicative and linguistic-cultural competencies. The article presents techniques for working with polycode texts.